Intrapartum fetal heart rate monitoring using a handheld Doppler versus Pinard stethoscope: a randomized controlled study in Dar es Salaam - Kamala BA; Kidanto HL; Wangwe PJ; Dalen I; Mduma ER; Perlman JM; Ersdal HL (Dove Medical Press, 2018)
Benjamin A Kamala,1,2 Hussen L Kidanto,3,4 Peter J Wangwe,2,5 Ingvild Dalen,3 Estomih R Mduma,3,6 Jeffrey M Perlman,7 Hege L Ersdal1,8 1Faculty of Health Sciences, University of Stavanger, Stavanger, Norway; 2Department of Obstetrics and Gynecology, Muhimbili National Hospital, Dar es Salaam, Tanzania; 3Department of Research, Stavanger University Hospital, Stavanger, Norway; 4School of Medicine, Aga Khan University, Dar es Salaam, Tanzania; 5Department of Obstetrics and Gynecology, Muhimbili University of Health and Allied Science, Dar es Salaam, Tanzania; 6Department of Research, Haydon Lutheran Hospital, Manyara, Tanzania; 7Department of Pediatrics, Weill Medical College, New York, NY, USA; 8Department of Anesthesiology and Intensive Care, Stavanger University Hospital, Stavanger, Norway Background: Fetal stethoscopes are mainly used for intermittent monitoring of fetal heart rate (FHR) during labor in low-income countries, where perinatal mortality is still high. Handheld Dopplers are rarely available and are dependent on batteries or electricity. The objective was to compare the Pinard stethoscope versus a new wind-up handheld Doppler in the detection of abnormal FHR. Materials and methods: We conducted a randomized controlled study at Muhimbili National Hospital, Tanzania, from April 2013 to September 2015. Women with gestational age ≥37 weeks, cephalic presentation, normal FHR on admission, and cervical dilatation <7 cm were included. Primary outcome was abnormal FHR detection (<120 or >160 beats/min). Secondary endpoints were time to delivery, mode of delivery, and perinatal outcomes. χ2, Fisher’s exact test, Mann–Whitney test, and logistic regression were conducted. Unadjusted and adjusted odds ratios were calculated with respective 95% confidence interval. Results: In total, 2,844 eligible women were assigned to FHR monitoring with Pinard (n=1,423) or Doppler (n=1,421). Abnormal FHRs were more often detected in the Doppler (6.0%) versus the Pinard (3.9%) arm (adjusted odds ratio =1.59, 95% confidence interval: 1.13–2.26, p=0.008). Median (interquartile range) time from abnormal FHR detection to delivery was comparable between Doppler and Pinard, ie, 80 (60,161) and 89 (52,165) minutes, respectively, as was the incidence of cesarean delivery (12.0% versus 12.2%). The incidence of adverse perinatal outcomes (fresh stillbirths, 24-hour neonatal admissions, and deaths) was similar overall; however, among newborns with abnormal FHR delivered vaginally, adverse outcomes were less incident in Doppler (7 of 43 births, 16.3%) than in the Pinard arm (10 of 23 births, 43.5%), p=0.021. Conclusion: Intermittent FHR monitoring using Doppler was associated with an increased detection of abnormal FHR compared to Pinard in a low-risk population. Time intervals from abnormal FHR detection to delivery were longer than recommended in both arms. Perinatal outcomes were better among vaginally delivered newborns with detected abnormal FHR in the Doppler arm. Keywords: fetal heart rate, perinatal outcomes, Pinard stethoscope, Doppler